Hubungan Hopelessness Loneliness dengan Future Anxiety pada Mahasiswa - Nisrina Alfy Subardi; Agus Salim; Ratna Yunita Setiyani Subardjo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the relationship between hopelessness and loneliness with future anxiety in college students. The method used is a quantitative approach with a correlational design. The research sample consisted of 200 students from various universities and domiciled in Yogyakarta. Data were collected through a questionnaire that measured the level of hopelessness, loneliness, and future anxiety. The research data were analyzed using multiple linear regression techniques. The results of hypothesis testing showed a significant positive relationship between hopelessness,  loneliness and future anxiety with a significance of 0.000. The coefficient of determination (R2) indicates that future anxiety can be explained by the hopelessness  and loneliness variable by 46,2% explained by feelings about the future, loss of motivation, and imagining individuals in the future. This finding confirms that the more individuals experience hopelessness, the higher the future anxiety. This research is expected to provide insight into the relationship between hopelessness, loneliness and future anxiety in college students, as well as a reference for students in anticipating and dealing with their problems.